Ensartinib in a primary pulmonary ALK-rearranged mesenchymal neoplasm harboring a novel HMBOX1::ALK fusion: a case report and literature review - Liang, Qi; Jiang, Xingyu; Zhou, Ziwei; Jiang, Yali; Ni, Siqi; Zhao, Tingyu; Zhang, Xiao; Xu, Huanhuan; Gong, Qixing; Liu, Lingxiang (Frontiers in Medicine, 2025)
Anaplastic lymphoma kinase (ALK) gene rearrangements have been increasingly detected in mesenchymal neoplasms. ALK-rearranged mesenchymal neoplasms occur mainly in superficial tissues but rarely in internal organs. Herein, we firstly report a primary lung lesion presenting as a rare ALK-rearranged mesenchymal neoplasm. The patient diagnosed with primary pulmonary ALK-rearranged mesenchymal neoplasm (PPAMN) received ensartinib as postoperative adjuvant therapy, achieving a disease-free survival of 10 months. Continuation of ensartinib as first-line treatment enabled him to benefit from a partial response, with a progression-free survival of 11 months. Second next-generation sequencing (NGS) revealed elevated HMBOX1::ALK abundance along with secondary NF2 mutation. After local radiotherapy combined with ensartinib continuation, his disease was temporarily stable for 7 months. Unfortunately, this disease became uncontrolled with an overall survival (OS) of 34 months. This is the first case of ALK-rearranged mesenchymal neoplasm manifested as a primary lung lesion and a novel HMBOX1::ALK fusion was identified by NGS. The family of ALK-rearranged mesenchymal neoplasms is expanding and ensartinib could be a potential treatment option for patients with HMBOX1::ALK. Repeated biopsy and NGS detection are critical to guide treatment selection at disease progression.